2015
DOI: 10.1016/j.cognition.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

More than one way to see it: Individual heuristics in avian visual computation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…In our experiment, also, the budgerigars required fewer trials to reach the training criterion. Our findings thus confirm that different bird species trained and tested on the same stimulus sets can behave quite differently, as was observed for the keas and pigeons in a visual grammar learning task (39). In that study pigeons and keas both attended to local features of the training stimuli; the species differed in which features were used and the consistency with which a specific strategy was used among individuals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our experiment, also, the budgerigars required fewer trials to reach the training criterion. Our findings thus confirm that different bird species trained and tested on the same stimulus sets can behave quite differently, as was observed for the keas and pigeons in a visual grammar learning task (39). In that study pigeons and keas both attended to local features of the training stimuli; the species differed in which features were used and the consistency with which a specific strategy was used among individuals.…”
Section: Discussionsupporting
confidence: 87%
“…Thus far, budgerigars have not been tested in an artificial grammar learning task, making it of interest to compare them to zebra finches. A comparison of species belonging to these two distinct clades also is of interest because the previously mentioned studies comparing another parrot species, the kea, with pigeons (also a different clade) revealed that these species used very different strategies to distinguish between two string sets consisting of different visual patterns (14,39). All keas showed the same consistent strategy, but the pigeons showed no consistent pattern at either the species or individual level (39).…”
mentioning
confidence: 99%
“…A key issue in AGL is that participants may show above-chance performance, but nonetheless have induced a grammar different from the exact intended “target” grammar the experimenters used to generate the stimuli ( van Heijningen et al, 2009 ; Fitch and Friederici, 2012 ; Ravignani et al, 2015 ). This would be particularly problematic if an alternate grammar at a lower level of grammatical complexity could be adopted and still yield “successful” performance, as observed in previous experiments with animals ( van Heijningen et al, 2009 ; Ravignani et al, 2015 ). To evaluate this possibility we analyzed our data using a multilevel Bayesian modeling framework, implemented in R (see ESM for a detailed description of our statistical framework).…”
Section: Resultsmentioning
confidence: 99%
“…Using these weights (which sum up to a total of 1), we identified the Akaike set : the set of all highest-ranked models summing up to a cumulative Akaike weight of at least 0.95 (Johnson and Omland, 2004; Ravignani et al, 2015), in order to provide a view on the robustness of the best-fitting model. By aggregating the Akaike weights in this way, we (i) gain the combined explanatory power of multiple models instead of just the best one, and (ii) counteract the volatility of the analysis: i.e., if there are relatively few models with a high Akaike weight in this Akaike set, and most of them share a particular feature, we have more confidence in the importance of this feature than by just exploring the single best model.…”
Section: Analysis and Results: Time Series Analysis For (Higher Ordermentioning
confidence: 99%